PENGARUH PRODUKSI DAN HARGA TERHADAP KONSUMSI BERAS DI KABUPATEN KERINCI - Putri, Osi Hayuni; Gunawan, Septian Indra (Aksara Public, 2018)
The agricultural sector is the primary sector and plays an important role for the national economy. One result of the agricultural sector is rice which is the staple food of Indonesian citizens. This study aims to determine the effect of simultaneous and partial production, and price of rice consumption Kerinci regency, as well as to analyze the variables that have the most dominant influence on rice consumption in Kerinci regency for the period of 2010 - 2015. Data analysis techniques used are multiple linear regression. The results showed simultaneously production and price variables significantly affect the consumption of rice in Kerinci regency in 2010 - 2015. Partially, the variables of rice production and consumption of rice did not affect the consumption of rice in Kerincitahun 2010 - 2015. Production and price variables have a positive and significant on the consumption of rice in Kerincitahun 2010 - 2015.